Economic Evaluation and Systematic Review of Publicly Available Workers' Compensation Practice Details and Mod Rate Calculators Applied to Upper Midwest Agriculture. Issue 1 (2nd January 2020) - Weichelt, Bryan; Pena, Anita Alves; Joyce, Jeffrey; Keifer, Matthew
ABSTRACT: Background : Agricultural employment is one of the most dangerous occupations in the United States. Workers' compensation coverage requirements for agricultural work vary from state to state, and experience modifier rates (E-mods) affecting insurance premiums sometimes vary drastically across state lines and according to claim severities and farm sizes. We proposed to develop an interactive software application that would educate farmers on the impact of employee time loss on annual E-mod factor change specific to their geographic location and farm size. Methods : We conducted a comparative analysis of workers' compensation formulations, including E-mods among Upper Midwestern states. We performed sensitivity analysis of the formulas to claim amount and payroll to highlight differences related to claim severity and to farm size. Results : The state to state variation and remarkable complexity of these formulas was confirmed. E-Mod factors are shown to increase substantially across states with both claim size and payroll, though are found to be similar across Wisconsin and Minnesota which were examined in detail. Conclusions : The findings confirm that creating a nationally applicable interactive educational software tool for farmers and ranchers to view hypothetical rate changes by inputting on-farm injury scenarios represents a significant challenge and that educational outreach coupled with the use of commercial software, especially as less costly options become available, may serve the role of minimizing misunderstandings by current producers as may other informational sources.